Optimalisasi Pendampingan Ibu Hamil Trimester III melalui Program Perencanaan Persalinan dan Pencegahan Komplikasi (P4K) untuk Mengurangi Kecemasan saat Persalinan - Muliatul Jannah; M Biomed; Atika Zahriah (LPPM Akbid Harapan Ibu Pekalongan, 2022)
Pregnancy is a beautiful period, but the major changes in the body with a short time often caused from some disturbances and complaints, that reduce enjoyment during pregnancy. Anxious feeling often occurs during pregnancy, especially in mothers who have unstable soul and reach a climax at the time of delivery. Women who experience pregnancy anxiety are more likely to experience labor complications. Health programs to reduce the occurrence of complications that can be implemented include the Delivery Planning and Complications Prevention Program. The Maternity Planning and Complications Prevention called (P4K) includes pregnancy exercises and preparation for childbirth. Physical exercise during pregnancy and preparation for childbirth can be done in safe planning and preparation for the possibility of complications during childbirth. The purpose to increase of knowledge for pregnant women to do exercises during pregnancy and plan physical exercise can reduce anxiety and prevent complications. Participants are third trimester in prenatal class, divided into 3 groups with the covid protocol, each of group maximum 8-9 people. The implementation of this community service collaboration with Purwosari Village, Sayung District, Demak Regency with 25 participants. The result of this program has plan to produce targeted outcomes, namely: Publications in newspapers and scientific journals.